The Digital Shopfloor- Industrial Automation in the Industry 4.0 Era : Performance Analysis and Applications - John Soldatos; Oscar Lazaro; Franco Cavadini (River Publishers, 2019)
The present book provides a comprehensive description of some of the most representative solutions that offered by these three projects, along with the ways these solutions can be combined in order to achieve multiplier effects and maximize the benefits of their use.